2020
DOI: 10.3390/ani10030413
|View full text |Cite
|
Sign up to set email alerts
|

Dropping the Ball? The Welfare of Ball Pythons Traded in the EU and North America

Abstract: Ball pythons (family Pythonidae) remain a commonly exploited species, readily available for purchase in North America and Europe. We assessed the housing conditions of more than 5000 Ball pythons across six exotic pet expositions and 113 YouTube videos. We scored provisions for hygiene, mobility, shelter, substrate and water provision, based on the Royal Society for the Protection of Animals (RSPCA) minimum guidelines. We found most entities involved in this commercial enterprise are not providing housing cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…Intensively managed captive-breeding operations for exotic pets are reported to involve poor welfare, because animals may be permanently held under conditions of deprivation involving restrictive and inappropriate enclosures, subjected to either stressful overcrowding or solitary confinement, and offered only minimal provisions of food and water [ 56 , 57 , 58 ]. Chronic or lifelong problems can result from some captive-breeding methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intensively managed captive-breeding operations for exotic pets are reported to involve poor welfare, because animals may be permanently held under conditions of deprivation involving restrictive and inappropriate enclosures, subjected to either stressful overcrowding or solitary confinement, and offered only minimal provisions of food and water [ 56 , 57 , 58 ]. Chronic or lifelong problems can result from some captive-breeding methods.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic disorders, commonly associated with domesticated companion animals, are also linked with exotic pet breeding. For example, artificial selection of reptiles is associated with the neurological disease “wobble syndrome” in royal python ( Python regius ) morphs, and can, amongst other problems, affect their ability to feed [ 58 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ball pythons have specific requirements regarding diet, lighting, hygiene, space, temperature and humidity [19]. Yet in a recent review involving more than 5000 individual Ball pythons in North America and Europe, D'Cruze et al [20] found that the entities involved in this commercial enterprise were not providing housing conditions that meet the minimum welfare recommendations, either in public or privately, for periods of time that could range from several days to many years. The same study found that vendors selling Ball pythons online and at pet expositions were not providing husbandry guidance for new owners.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of failing to meet these requirements or provide adequate information on how to do so can negatively impact reptile welfare, resulting in disease, injuries, stress-related behaviours [21], mental suffering and mortalities associated with poor husbandry. In addition, intense breeding selection of gene mutations to create novel morphs leads to inbreeding, resulting in genetic disorders with consequential health issues [20].…”
Section: Introductionmentioning
confidence: 99%